NEUROGENIN3 REGULATES SOHLH1 DURING SPERMATOGNESIS IN MICE - X. Guo; S. Li; B. Du; Z. Li; W. Yang; W. Dong; J. Liu; Z. Zheng (Journal of Animal and Plant Sciences, 2015)
Spermatogonial stem cells (SSCs) are tissue-specific stem cells in testis, and differentiation of SSCs contributes to spermatogenesis and male fertility. However, little is known about factors regulating spermatogonial differentiation. Neurogenin3 (Ngn3), a class B basic helix-loop-helix (bHLH) transcription factor, recognized for its role in promoting the development of neurons in the hypothalamus, specifically expresses in undifferentiated spermatogonia and is a critical differentiation factor of mammalian stem and progenitor spermatogonia. Sohlh1 (spermatogenesis and oogenesis specific basic helix-loop-helix 1) is regarded as a key factor in spermatogenesis, which promotes the expression of Kit, the marker of differentiated spermatogonia. In this study, we firstly confirmed that the expressionlevelofNgn3 is decreased in Sohlh1-/- mice by real-time PCR and western blot, and revealed the associationbetweenNgn3and Sohlh1. We then showed that Ngn3 could bind to the promoter of Sohlh1andincrease the transcription of Sohlh1 by ChIP and luciferase reporter gene assay. Lastly, we demonstrated that the protein of Ngn3 and Sohlh1 could bind together in wild type testis by immune precipitation. In conclusion, our study showed the association between Ngn3 and Sohlh1 for the first time. Ngn3 may regulate spermatogenesis by binding with Sohlh1, which may be the direct target of Ngn3 in differentiation of SSC.
Keywords: Ngn3; Sohlh1; spermatogenesis; transcription factor